Taking it to the next level: lumbar radiculopathy from thoracic nerve schwannoma - Anene Ukaigwe; Akintomi Olugbodi; Richard L. Alweis (Greater Baltimore Medical Center, 2015)
Compression or irritation of the sciatic nerve and its branches, the common fibular and tibial nerves, causes sciatica which is a common syndrome characterized most often by radiating pain from the lower back down the legs and also manifesting as sensory and motor deficits. Sciatica is a common presentation of lumbosacral disc prolapse and degenerative disease of the lumbar spine in ambulatory settings. Schwannomas rarely cause sciatica; hence, it is seldom considered in evaluation of a patient with radiculopathy. Our patient presented with lumbar radiculopathy, mild degenerative changes on lumbar magnetic resonance imaging (MRI) scan, and failed conservative treatment. Myelopathy was confirmed with electromyogram (EMG). Thoracolumbar spine MRI revealed the schwannoma in the thoracic region. He recovered neurologic function after tumor excision. This case highlights the diagnostic challenge that may arise in evaluating a patient with lumbar radiculopathy, negative lumbosacral spine imaging, and failure of conservative therapy.